Предмет: Алгебра,
автор: likadudina1322
упростите выражение: соs⁶x+sin⁶x-sin²x-cos²x.
Ответы
Автор ответа:
0
Ответ:
-(3/4)sin²2x
Объяснение:
(cos²x)³+(sin²x)³-(sin²x+cos²x)=(cos²x+sin²x)(cos⁴x+sin⁴x-sin²xcos²x)-1=
=1*((cos²x+sin²x)²-3sin²xcos²x)-1=1-3sin²xcos²x-1=-3sin²xcos²x=
=-(3/4)sin²2x
Автор ответа:
0
Ответ:
соs⁶x+sin⁶x-sin²x-cos²x
cos²x(cos^4(x) - 1) + sin²x(sin^4(x) - 1)
Распишем выражения в скобках как разности квадратов:
cos²x(cos²x - 1)(cos²x + 1) + sin²x(sin²x - 1)(sin²x+1)
-cos²x(-cos²x + 1)(cos²x + 1) - sin²x(-sin²x + 1)(sin²x+1)
-cos²x + 1 = sin²x; -sin²x + 1 = cos²x
-cos²x(sin²x)(cos²x + 1) - sin²x(cos²x)(sin²x+1)
-cos²x*sin²x(cos²x + 1) - sin²x*cos²x(sin²x+1)
-(cos²x*sin²x)(cos²x + 1 + sin²x+1)
cos²x + sin²x = 1
-(cos²x*sin²x)*(3)
-3cos²x*sin²x
Похожие вопросы
Предмет: Русский язык,
автор: sofiadenis
Предмет: Русский язык,
автор: musaeva21111
Предмет: Английский язык,
автор: natisi2017
Предмет: Английский язык,
автор: Lopk7
Предмет: Математика,
автор: ivasenkob19